Correlates of support for a nicotine-reduction policy in smokers with 6-week exposure to very low nicotine cigarettes. Issue 3 (1st November 2018) - Denlinger-Apte, Rachel L; Tidey, Jennifer W; Koopmeiners, Joseph S; Hatsukami, Dorothy K; Smith, Tracy T; Pacek, Lauren R; McClernon, F Joseph; Donny, Eric C
Abstract : Background: The US Food and Drug Administration recently issued an advanced notice of proposed rule-making for reducing the nicotine content in cigarettes to a minimally addictive level. Very little is known about whether use of very low nicotine content (VLNC) cigarettes affects support for a nicotine reduction policy. Objective: This study examined the effects of using VLNC versus usual brand (UB) cigarettes on support for a nicotine reduction policy and determined whether participant characteristics and responses to VLNC cigarettes were associated with policy support. Methods: Participants from a cigarette trial who were assigned to either 0.4 mg nicotine/g tobacco research cigarettes or their UB for 6 weeks were asked about their support for the policy. χ 2 tests were used to compare support for the policy between cigarette conditions and logistic regression analyses were conducted to assess covariates associated with policy support. Findings: Policy support did not differ by condition. After 6 weeks of using VLNC cigarettes, 50% of participants supported the policy, 26% opposed and 24% responded 'Don't Know'. Support was higher among those adherent to smoking only VLNC cigarettes (65%) compared with those who were non-adherent (44%). Older participants and those interested in quitting had increased odds of support. Cigarette satisfaction, perceived harm and perceived nicotine content were not significantly associated with support. Conclusions: Smoking VLNC cigarettes did not affect support for a nicotine reduction policy. Understanding predictors of policy support and opposition will help public health officials to maximise the public health acceptance and impact of this policy (ClinicalTrials.gov Identifier: NCT01681875 Post-Results).